(untitled) (Docentes 2.0 Journal, 2025)
Language development in children is a fundamental process that directly influences their ability to communicate, think, and interact with their environment. Its stimulation strengthens cognitive, social, and emotional skills, essential for meaningful learning and effective communication. The objective of this research was to analyze the level of knowledge possessed by seventh-year students of the Early Childhood Education program at the Distance and Online Studies Unit of the National University of Loja regarding methodological strategies for language development in children, identify the methodological strategies they are familiar with, and describe their strengths and weaknesses. The study was conducted using a quantitative paradigm, a non-experimental design, and correlational analysis with a cross-sectional scope. A structured survey was administered to a population of 110 students, who comprised the sample. The results show that seventh-year students have a high level of knowledge of methodological strategies, especially those related to play, stories, and songs. However, some weaknesses in its practical application were identified, such as a lack of financial resources and limited practical training. Therefore, although the theoretical knowledge is solid, it is necessary to strengthen spaces for pedagogical practice that allow future teachers to apply these methodological tools more frequently. This study provides empirical evidence that can guide the improvement of teacher training and curriculum design in early childhood education programs.